2023
DOI: 10.1002/anie.202217470
|View full text |Cite
|
Sign up to set email alerts
|

Diradical B/N‐Doped Polycyclic Hydrocarbons

Abstract: Heterocyclic diradicaloids with atom‐precise control over open‐shell nature are promising materials for organic electronics and spintronics. Herein, we disclose quinoidal π‐extension of a B/N‐heterocycle for generating B/N‐type organic diradicaloids. Two quinoidal π‐extended B/N‐doped polycyclic hydrocarbons that feature fusion of the B/N‐heterocycle motif with the antiaromatic s‐indacene or dicyclopenta[b,g]naphthalene core were synthesized. This quinoidal π‐extension and B/N‐heterocycle leads to their open‐s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 77 publications
0
31
0
Order By: Relevance
“…Lewis acidity is an intriguing feature of this kind of B-containing organic radical, because it provides a new scaffold to achieve modulation of the radical characteristic and (anti)aromaticity by intermolecular Lewis acid-base coordination. 29,30,45 These molecular ladders composed of two distant and well-separated triphenylborane groups offer the possibility of gaining insight into the electronic effects of aromatic rings on the antiaromatic π-skeleton and Lewis coordination. Titration experiments were performed on BML1 and BML2 and monitored by UV/Vis absorption spectroscopy (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lewis acidity is an intriguing feature of this kind of B-containing organic radical, because it provides a new scaffold to achieve modulation of the radical characteristic and (anti)aromaticity by intermolecular Lewis acid-base coordination. 29,30,45 These molecular ladders composed of two distant and well-separated triphenylborane groups offer the possibility of gaining insight into the electronic effects of aromatic rings on the antiaromatic π-skeleton and Lewis coordination. Titration experiments were performed on BML1 and BML2 and monitored by UV/Vis absorption spectroscopy (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1a, including neutral boron-containing π-monoradicals (I-III) and π-diradicaloids (IV-VII). [23][24][25][26][27][28][29][30][31] For instance, Yamaguchi et al elegantly developed the highly stable π-radical I that contains a boron atom in a planarized triphenylmethyl radical framework, and demonstrated its potential utility as an ambipolar semiconductor in singlecrystal field-effect transistors and as an emitting material in organic light-emitting diodes. 23,24 Wang et al reported dioxoborocyclic monoradical III and diradical VII as new kinds of boron-containing π-radicals, which feature an intramolecular ion pairing state via Lewis acid-induced single electron transfer.…”
Section: Introductionmentioning
confidence: 99%
“…The theoretical ΔE SÀ T were À 12.68 and À 6.42 kcal mol À 1 for compounds 1 and 2, respectively, agreeing with the experimental trend. Interestingly, the DFT calculations (see reference [10] and its Supporting Information) disclosed that the substitution of the antiaromatic sindacene and dicyclopenta[b,g]naphthalene core (compounds 3 and 4, respectively) results in a decrease of the ΔE SÀ T with respect to their B/N doped analogues. The decrease in the gap between the singlet and triplet diradicaloid states is readily explained by the expansion of the π-conjugation going from compound 1 to 2, and going from compounds 3 and 4 to 1 and 2, respectively, which decreases the exchange interaction energy largely determining the ΔE SÀ T .…”
Section: Methodsmentioning
confidence: 99%
“…[9] In a recent research article, Guo et al synthesized two B/N-doped quinoidal PAHs, compounds 1 and 2 (Figure 1a), that can be seen as the fusion of B/N doped PAHs with the antiaromatic s-indacene or dicyclopenta[b,g]naphthalene core, respectively. [10] This new strategy to design diradicaloids is essentially playing on the cooperative effect of the boron and nitrogen atoms to perturb the electronic structure of the PAHs and to tune its diradical character. Single crystals of compound 2 were grown and revealed that bond [10] ) and 2 (5 in [10] )) and their all-carbon (heterocyclic-free) analogues (3 (6 in [10] ) and 4 (7 in [10] )); b) X-ray crystal structure of 2 with thermal ellipsoids shown at 50 % probability; c) Resonance structures in closedshell and open-shell forms for the unsubstituted compound 1.…”
mentioning
confidence: 99%
“…The doping of organic compounds with B and N atoms, the combination of which being isoelectronic and isosteric with CC couples, has evolved into a powerful approach for accessing novel materials with modified, often intriguing properties. 4,5 Application of this BN/CC isosterism concept to conjugated polymers, however, is still in its infancy. 6–8 Our group has developed a series of BN-doped polymers with direct BN bonds, including a BN analogue of poly( p -phenylene vinylene) (PPV) B 6 b and the first examples of the poly(iminoboranes) C , which are polyacetylene isosteres.…”
mentioning
confidence: 99%